1997
DOI: 10.1007/bf01411305
|View full text |Cite
|
Sign up to set email alerts
|

Giant intrasacral schwannomas: Report of six cases

Abstract: Only 4 of the 30 previously reported cases of giant sacral schwannomas have been studied with Magnetic Resonance Imaging (MRI). We are reporting 6 more cases, 5 of which had MRI studies. There were 5 women and 1 man (average age 45 years) with long lasting symptoms consisting of lumbosacral and radicular pain accompanied by urinary disturbances and dysaesthetic sensations in the lower limbs. CT clearly defined sacral bone involvement but poorly demonstrated intraspinal tumour extension which was more evident i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
1
4

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 16 publications
0
46
1
4
Order By: Relevance
“…This is typically anteriorly into the pelvic cavity [3,5,9,11,12] but can be posteriorly [2] or combined [6,8]. In contrast, giant presacral schwannomas (GPSS), as illustrated in this small series and a recent case report [12], presumably arise from a peripheral nerve in or adjacent to an anterior sacral foramen.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This is typically anteriorly into the pelvic cavity [3,5,9,11,12] but can be posteriorly [2] or combined [6,8]. In contrast, giant presacral schwannomas (GPSS), as illustrated in this small series and a recent case report [12], presumably arise from a peripheral nerve in or adjacent to an anterior sacral foramen.…”
Section: Discussionmentioning
confidence: 87%
“…The largest published series of 13 cases of GSS collected over 33 years predated the routine use of MR imaging [3]. A more recent study describes the use of MR imaging in 5 of 6 cases but, as in many of the reported cases, the tumours were primarily intra-rather than presacral in origin [9]. The purpose of this report is to describe the MR features of giant presacral schwannomas (GPSS) which arise on the surface rather than within the sacrum.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Presacral schwannomas are rare accounting for 1-5% of spinal schwannomas [2][3][4]. Less than 30 cases of presacral schwannoma have been reported in English literature [5].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are only 2 cases previously reported of AS involving cauda equina [1, 2], an exceedingly rare schwannoma subtype for an extremely uncommon location. Although reported to affect head and neck, cervical region, limbs, pelvis, and retroperitoneum [1–5], it is uncommon is the spinal cord [610] but cauda equina involvement is exceptional.…”
Section: Introductionmentioning
confidence: 99%